2019
DOI: 10.1093/abbs/gmz053
|View full text |Cite
|
Sign up to set email alerts
|

YAP mediates the positive regulation of hnRNPK on the lung adenocarcinoma H1299 cell growth

Abstract: Lung cancer is the leading cause of cancer death worldwide, and non-small cell lung cancer (NSCLC) accounts for 80%–85% of diagnostic cases. The molecular mechanisms of NSCLC pathogenesis are not well understood. Heterogeneous nuclear ribonucleoprotein K (hnRNPK) is a multifunctional protein that regulates gene expression and signal transduction and closely associated with tumorigenesis, but its mechanism of action in the pathogenesis of NSCLC is unclear. In this study, we observed that the expression pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Hippo signaling pathway. MST1/2 is the core kinases of the classical Hippo signaling pathway in mammals (13), which also plays a key role in the immune microenvironment by regulating the adhesion and trafficking of immune cells (14). A paralogous gene of the EVA1A gene is EVA1B, which both belong to the EVA1 family.…”
Section: Introductionmentioning
confidence: 99%
“…Hippo signaling pathway. MST1/2 is the core kinases of the classical Hippo signaling pathway in mammals (13), which also plays a key role in the immune microenvironment by regulating the adhesion and trafficking of immune cells (14). A paralogous gene of the EVA1A gene is EVA1B, which both belong to the EVA1 family.…”
Section: Introductionmentioning
confidence: 99%
“…One report revealed that lncRNA pancEts-1 could facilitate neuroblastoma progression by HNRNPK-mediated the stabilization of β-Catenin [35]. Xu et al proved that HNRNPK promoted cell colony formation and proliferation in lung adenocarcinoma cells [36]. Peng et al reported that HNRNPK contributed to cell invasion, migration, and proliferation via regulation of the alternative splicing of CD44E in GC cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Colony formation assay were carried out as previously described . Cells after treatments were cultured in 6-well plate at a density of 2 × 10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%